PERSEPSI REMAJA MASJID TERHADAP BANK SYARIAH: SURVEI PADA REMAJA MASJID AL-HIDAYAH BLOK C16 RW 32TAMBUN BEKASI - Maesaroh, Juleha; Widyananto, Arief (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2016)
This study aims to determine the perception of youth mosque to Islamic banks in the Al Hidayah Mosque Block C16 Rw. 32 Tambun Bekasi. This study was a qualitative study with phenomenological approach, with this approach researchers interviewed youth mosque in the mosque youth perception towards Islamic banks. Based on the results of in-depth interview research about adolescent perception of the mosque to the Islamic banks that the 3 (three) of respondents who have a very good perception of the Islamic Bank. This is due to respondents' knowledge on Islamic bank, and one respondent who become customers of Islamic banks. Then 2 (two) of respondents who have a fairly good perception towards Islamic Bank. It is caused by a lack of knowledge of Islamic banks.